PENGARUH LIKUIDITAS, PROFITABILITAS DAN PENJUALAN TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Nunuk Idamanti (Universitas muhammadiyah malang, 2016)
The research aims to analyse the effect of liquidity, profitability, and sales growth on stock price. Samples used in this study are food and beverage companies listed in the Indonesian Stock Exchange during 2010-2014 periods. Multiple linear regression method used to anlyse the effect of CR, ROE, and Sales Growth on Stock Price. The results showed that CR, ROE, and Sales Growth have a significant effect on Stock Price.